Resonance capture at arbitrary inclination - II. Effect of the radial drift rate - Namouni, F.; Morais, M. H. M. [UNESP] (Oxford Univ Press, 2017)
The effect of the radial drift rate on mean motion resonance capture is studied for prograde, polar and retrograde orbits. We employ the numerical framework of our earlier exploration of resonance capture at arbitrary inclination. Randomly constructed samples ofmassless particles are set to migrate radially from outside the orbit of a Jupiter-mass planet at different drift rates totalling more than 1.6 x 10(6) numerical simulations. Slower drift rates reduce overall capture probability especially for prograde orbits and enhance capture at specific initial inclinations of high-order resonances such as the outer 1: 5, 1: 4, 1: 3, 2: 5, 3: 7, 5: 7. Global capture is reduced with increasing eccentricity at all inclinations as high-order resonances capture more particles that are subsequently lost by disruptive close encounters with the planet. The relative efficiency of retrograde resonances at long-lived capture with respect to prograde resonances is explained by the reduced effect of planet encounters as such events occur with a shorter duration and a higher relative velocity for retrograde motion. Capture in the co-orbital 1: 1 resonance is marginally affected by the radial drift rate except for nearly co-planar retrograde eccentric orbits whose capture likelihood is increased significantly with slower drift rates. An unexpected finding is the presence of a dynamical corridor for capture in high-order inner prograde resonances with initial inclinations in the range [50 degrees, 80 degrees] especially at the inner 5: 2 resonance whose capture likelihood peaks at 80 per cent to 90 per cent depending on the initial eccentricity.
Keywords: celestial mechanics; comets: general; Kuiper belt: general; minor planets, asteroids:general; Oort Cloud